A wireless and wearable measurement system for human body electrostatic monitoring application. (March 2018) - Wang, Yao-Chin; Lin, Nan-Chun; Lin, Bor-Shyh
Abstract: In particular, electrostatic discharge (ESD) and electric overstress (EOS), for the production assembly, were concluded as the common problems for all electronic manufacturers in worldwide. Uncontrollable and invisible electrostatic discharge events were the major problems, because production quality was performed by well-controlled electrostatic discharge and electric overstress. Currently, it was passively managed the electrostatic grounding path by a connection on the assembly line, the correct wearing of electrostatic ground wrist/ankle straps, and the installation of static ionizers on top of the riskiest workstations to dissipate the electrostatic energy, with the regular check of electrostatic discharge being eliminated or dissipated by static ionizers. The above methods could merely detect fixed locations, but could not real time detect the electrostatic conditions of an operator and record the related events for the database analysis. In order to improve the above issue, the study proposed a wearable and wireless human body electrostatic monitoring system to real-time detect the ESD event of an operator and record the ESD events for the database analysis. By using the real-time alert mechanism, the proposed system could effectively prevent these ESD damages: (1) could inform the operator to immediately discharge the cumulative electric charge; (2) could be transmit to the back-end host system via Bluetooth to make up the careless mistake in the operation, and this alert could be regarded as the second prevention; (3) could be recorded in database for successive data analyses. Finally, the proposed system was also validated and applied in the production assembly and the experimental results indicated that it could exactly provide an effective way to reduce the influence of ESD/EOS.